2019
DOI: 10.1002/mus.26746
|View full text |Cite
|
Sign up to set email alerts
|

Utility of electrodiagnostic studies in patients referred with a diagnosis of polyneuropathy

Abstract: Background Peripheral polyneuropathies (PN) are common neuromuscular conditions. The role of electrodiagnostic study (EDX) in diagnosis of PN is not well‐defined. Methods We performed a retrospective chart review of patients referred for EDX evaluation of PN. Results Of 162 patients analyzed, 23 had pure peripheral neuropathy (pPN; 14.2%), 29 had peripheral neuropathy and another diagnosis (PN+; 17.9%), 51 had an alternative diagnosis (nonPN; 31.5%), and 59 had normal studies (36.4%). In univariable analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
4
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
3
4
1
1
Order By: Relevance
“…This is consistent with two previous studies that showed that only 0.4% of DSP patients and 0.6% of peripheral neuropathy cases had a demyelinating neuropathy. 4,6 One prior study suggested that inflammatory and demyelinating etiologies accounted for 20% of all peripheral neuropathies, but our data do not support this finding. 13 We found that only 5.5% of chronic acquired demyelinating neuropathy patients presented with a DSP phenotype, and none of them were ultimately diagnosed with typical CIDP.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…This is consistent with two previous studies that showed that only 0.4% of DSP patients and 0.6% of peripheral neuropathy cases had a demyelinating neuropathy. 4,6 One prior study suggested that inflammatory and demyelinating etiologies accounted for 20% of all peripheral neuropathies, but our data do not support this finding. 13 We found that only 5.5% of chronic acquired demyelinating neuropathy patients presented with a DSP phenotype, and none of them were ultimately diagnosed with typical CIDP.…”
Section: Discussioncontrasting
confidence: 97%
“…This policy statement specifically alludes to the importance of identifying chronic inflammatory demyelinating polyneuropathy (CIDP), a disabling and potentially treatable condition for which EDX is foundational to the diagnosis 5 . Other studies have shown that the prevalence of demyelinating neuropathies among patients referred for peripheral neuropathy is low 4,6 . However, this is to be expected, since CIDP is a rare disease compared to DSP 7 …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…2-5 Consequently, the role of EDx studies in evaluation of PN remains unsettled and, at present, is not optimally addressed by existing practice parameters.The study by Ginsberg and Morren in this issue of the Journal has advanced our knowledge and understanding on the issue of the value of EDx studies for suspected polyneuropathy. 6 The authors retrospectively analyzed 162 patients referred for EDx studies for the diagnosis of "peripheral polyneuropathy" at a large tertiary institution over a 1-year period. Only a third of patients were found to have PN on EDx studies and, of these patients, more than half had additional neuromuscular diagnoses.…”
mentioning
confidence: 99%
“…The study by Ginsberg and Morren in this issue of the Journal has advanced our knowledge and understanding on the issue of the value of EDx studies for suspected polyneuropathy . The authors retrospectively analyzed 162 patients referred for EDx studies for the diagnosis of “peripheral polyneuropathy” at a large tertiary institution over a 1‐year period.…”
mentioning
confidence: 99%